PENGARUH STATUS GIZI AWAL DAN KONSUMSI CHLORELLA GROWTH FACTOR TERHADAP KELUHAN KLINIS PENDERITA DEMAM BERDARAH DENGUE - Gina Apriani; Hardinsyah Hardinsyah; Yekti Hartati Effendi (Jurnal Gizi dan Pangan, 2010)
The objective of this study was to analyze the effect of pre-nutritional status and consumption of Chlorella Growth Factor (CGF) on symptom of Dengue Hemorrhagic Fever (DHF). Design of this study was a randomized clinical trial with 37 subjects of intervention group and 37 subjects of control group. The subjects were DHF in-patient of economic class of Karya Bhakti Hospital. The criteria for subjects were DHF in-patients (grade II and III), age ≥ 17 years, fever up to 7 days, serology Dengue Ig M (+), platelet <100.000/mm3, not pregnant and not suffering from immune impaired diseases. The result show that effect of pre-nutritional status (p> 0.01) was not significant, but the effect CGF consumption was significant (p< 0.01) on clinical symptom of DHF. This implies that CGF reduced the symptom severity of DHF. Further studies required for identify the actual bioactive components of CGF effects on DHF; and effect of selected nutritional biomarkers on DHF.